Impact of the Crisis as a Result of COVID-19 on the Global Competitiveness - Marikina, Maria (Research Papers, 2021)
The object of this article is the world economy after the onset of the COVID-19 pandemic. The current situation is characterized by a serious economic crisis and uncertainty about future economic development. The question of scientific interest is how does the COVID-19 pandemic affect the competitiveness of the economies? This is the subject of research. The thesis is that in terms of competitiveness, small economies are better able to cope with the challenges of the crisis imposed by COVID-19. The aim is to reach an analysis of this issue for the world economy and for Bulgaria, and to make specific recommendations for our country.